2015
DOI: 10.1108/bfj-12-2013-0359
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ views on the status of the fish quality and safety regulatory schemes

Abstract: Purpose – The purpose of this paper is to explore the views of the primary and the secondary stakeholders on the current functioning of the fish quality and safety regulatory system in Oman. Design/methodology/approach – The views on the fish quality and safety regulatory governance mechanism were elicited using a questionnaire survey. Findings – Although specific benefits derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…With regard to SPS measures, Neeliah et al (2012), found that such measures did not act as a major barriers for Mauritian fish exports to the EU market. In a local context, the present finding is also consistent with the results obtained from the qualitative survey by Qatan et al (2015) where the industry representatives and the management authority reported that rejections from the EU market had become rare after the adoption of the HACCP system. Furthermore, it is reported by the authority that the highest number of notifications that were launched in 2005 and 2006 involved only two establishments.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With regard to SPS measures, Neeliah et al (2012), found that such measures did not act as a major barriers for Mauritian fish exports to the EU market. In a local context, the present finding is also consistent with the results obtained from the qualitative survey by Qatan et al (2015) where the industry representatives and the management authority reported that rejections from the EU market had become rare after the adoption of the HACCP system. Furthermore, it is reported by the authority that the highest number of notifications that were launched in 2005 and 2006 involved only two establishments.…”
Section: Discussionsupporting
confidence: 90%
“…Fish export creates competition between local and foreign consumers. To promote efficiency and fairness in relation to pricing and the distribution, and improve safety and quality of seafood products a central wholesale fish market with electronic auctioning system and other modern services has been in operation since April 2014 at Al-Filaij, a village of Barka in Al-Batinah Governorate (Al-Busaidi et al, 2016;Qatan et al, 2015). In addition, to maintain domestic market stability and satisfy local demand MAF has implemented export ban on selected preferred species in recent years ( Table 1).…”
Section: Fish Exports and The Eu Ban: A National Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicates that a 1% increase in the relative price, other things being equal, will stimulate a 1.44% increase in the export-supply to the EU market. It also reflects the fact that the price of seafood products in the EU market was attractive to encourage producers to supply their products relative to domestic price and is consistent with the notion of highvalue market as labeled by others (Qatan et al, 2015). In addition, the result in relation to positive growth rate of price compared with quantity in the EU market factor signals the importance of the price factor in this market.…”
Section: Model Diagnosticssupporting
confidence: 62%
“…The fulfillment of quality standards and safety of food products will facilitate the processing industry to obtain a product certificate that is expected to be a guarantee of product quality to be able to penetrate the wider market (Reardon, 1999 (Yuwono et al, 2012). The socialization of quality control regulations to the processing industry will bring positive changes to the quality and safety of seafood products (Qatan et al, 2015).…”
Section: Some Cracker Processors Inmentioning
confidence: 99%